2021
DOI: 10.1016/j.jaclp.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Psychiatric Emergency Service Volume and Hospital Admissions

Abstract: Background During the COVID-19 pandemic, there have been an increasing number of emergency department (ED) visits for behavioral health reasons, even as overall ED volumes have decreased. The impact of the pandemic and related public health interventions on specialized psychiatric emergency services has not been described. These services provide high intensity care for severely ill patients who are likely to be homeless and underserved. Objective We describe the change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
1
23
1
1
Order By: Relevance
“…Counter to expectations, however, in the US and elsewhere, visits for emergency psychiatric care fell in spring 2020 (Holland et al, 2021 ). In addition, a report on three specialty psychiatric emergency centers in the US finds an 8 to 9 percent drop in psychiatric emergencies after March 15, 2020 (Simpson et al, 2021 ). This decline coheres with the broader observation nationwide of avoidance of health care visits unrelated to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Counter to expectations, however, in the US and elsewhere, visits for emergency psychiatric care fell in spring 2020 (Holland et al, 2021 ). In addition, a report on three specialty psychiatric emergency centers in the US finds an 8 to 9 percent drop in psychiatric emergencies after March 15, 2020 (Simpson et al, 2021 ). This decline coheres with the broader observation nationwide of avoidance of health care visits unrelated to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have assessed the use of mental health resources, especially during the first wave of the pandemic. Most evidence relies on qualitative reports from populations of service users or from data coming from limited settings, i.e., emergency departments [ 45 , 46 , 47 , 48 ]. An in-depth description of the use of mental health services during the COVID-19 pandemic is necessary in order to delineate new pathways to care and to develop supportive interventions for the general population [ 11 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies highlighted that the number of admissions to psychiatric care facilities showed trends similar to the pre-COVID-19 outbreak period ( 39 ). This result could be due to an adaptation of mental services to give help during the pandemic, especially implementing digital mental health services ( 40 ), while it is in contrast with other findings, e.g., those concerning the decrease of new accesses to psychiatric emergency units ( 41 43 ). Based on the stated above, access to care during the COVID-19 emergency should be further investigated since it represents a complex issue that relies on several possible determinants ( 44 ).…”
Section: Discussionmentioning
confidence: 70%